New naturally occurring mineral phases from the Krasno - Horni Slavkov area, western Bohemia, Czech Republic - Sejkora,J.; Skoda,R.; Ondrus,P. (Journal of the Czech Geological Society, 2006)
This paper presents description of eleven phases - probably new mineral species - from Krasno - Horni Slavkov, western Bohemia, Czech Republic. The phases characterized are mainly supergene phosphates. All up-to-now available physical and chemical data for individual phases and references to appropriate literature are given.
Keywords: New natural phases; supergene minerals; phosphates; Krasno; Horni Slavkov; Czech Republic